2016
DOI: 10.1097/mjt.0b013e31828d4610
|View full text |Cite
|
Sign up to set email alerts
|

A Taurolidine–Citrate–Heparin Lock Solution Effectively Eradicates Pathogens From the Catheter Biofilm in Hemodialysis Patients

Abstract: Catheter-related bacteremia (CRB) is a typical complication of hemodialysis catheter use. Catheter lumen colonization by pathogens is regarded as a direct cause of CRB. Once settled, the catheter biofilm increases the risk of developing infection, thus necessitating insertion replacement and antibiotic treatment. The study assessed the self-sufficient efficacy of taurolidine-citrate-heparin lock solution in eradicating catheter biofilm bacteria and keeping it sterile in patients on hemodialysis. Twenty-nine ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Taurolidine solutions have been successfully proven as a catheter-lock agent to prevent catheter-related bloodstream infections in patients on home parenteral nutrition [18,19], in central venous catheters in children with cancer [20], and in hemodialysis patients [21]. By designing our study, we aimed to gain more insight on the potential use of taurolidine as alternative to commonly used topical antimicrobials, e.g., minocycline.…”
Section: Discussionmentioning
confidence: 98%
“…Taurolidine solutions have been successfully proven as a catheter-lock agent to prevent catheter-related bloodstream infections in patients on home parenteral nutrition [18,19], in central venous catheters in children with cancer [20], and in hemodialysis patients [21]. By designing our study, we aimed to gain more insight on the potential use of taurolidine as alternative to commonly used topical antimicrobials, e.g., minocycline.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction in CR-BSI rates using lock solution has been evidenced in various trials and meta-analyses published recently, yet the best prophylactic lock therapy option is still the subject of study (Silva et al, 2012;Filiopoulos et al, 2011;Weijmer et al, 2005;Zwiech et al, 2016;Solomon et al, 2010;Murray et al, 2014;Takla et al, 2007;Vercaigne et al, 2016;Maki et al, 2011;Dogra et al, 2002;Kim et al, 2006;Nori et al, 2006; Al-Hwiesh and -Rahman, 2007;Campos et al, 2011;Moran et al, 2012;Moore et al, 2014;Hemmelgarn et al, 2011;Wasse, 2008). In this study, the use of prophylactic lock therapy was studied only in catheters tunneled for HD, with a follow-up of at least 6 months, comparing solutions containing antibiotics (gentamicin + cefazolin) versus antimicrobial solutions (taurolidine + citrate); these solutions presented similar results in reducing CR-BSI and ESI.…”
Section: Discussionmentioning
confidence: 99%
“…However, 17 of these 28 patients had a relapse of catheter colonization with a median free interval of 70 days (range 2-101 days). In one of the above-noted studies, 21 23 patients who only had growth from catheter-drawn blood cultures of coagulase-negative staphylococci or Staphylococcus aureus then had their hemodialysis catheters locked once with a combination of taurolidine, citrate, and urokinase and then locked after each dialysis session with a combination of taurolidine, citrate, and heparin. When these patients had repeat catheter-drawn blood cultures after removal of the locking solution 34±8 days later, none of these cultures had microbial growth.…”
mentioning
confidence: 98%
“…Other investigators found that all 26 patients using either temporary or permanent hemodialysis catheters dialyzed for 51 ± 35 days had blood cultures growing predominantly coagulase-negative staphylococci drawn through catheter lumens after discarding heparinlocking solutions. 21 Three of the 26 had concomitant percutaneously drawn blood cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation